Wearing Occlusive Gloves Increases the Density of Staphylococcus aureus in Patients with Hand Eczema - Line Brok Nørreslet; Sofie Marie Edslev; Esben Meulengracht Flachs; Niels Erik Ebbehøj; Paal Skytt Andersen; Tove Agner (Medical Journals Sweden, 2021)
Hand eczema is frequently colonized with Staphylococcus aureus. Some patients with hand eczema wear occlusive gloves regularly; however, the effect of this on the density of S. aureus is unexplored. The aim of this study is to examine the effect of occlusive gloves on the density of S. aureus sampled from the hands of patients with hand eczema. In an experimental set-up, patients with moderate-to-severe hand eczema wore an occlusive glove on one hand for 4 h with a 30-min break. Bacterial swabs were collected from the most severe eczema lesion on the hand before and immediately after glove exposure. S. aureus colony-forming units were counted and log-transformations used for comparison of before- and after-values. Among 30 patients, 19 (63%) were colonized with S. aureus. After glove occlusion S. aureus colony-forming units increased by a factor of 1.72 (p < 0.01). In conclusion, the density of sampled S. aureus on eczematous skin after prolonged wearing of occlusive gloves is greatly increased.